HAZARD is over! Project HAZARD on seaport safety and security in the Baltic Sea Region 2016–2019 - Lauri Ojala; Mikko Harteela; Oskari Kajander; Minna-Liina Ojala; Jarmo Malmsten (Turun yliopisto, 2025)
HAZARD was an international EU-funded project to mitigate the effects of emergencies in major seaports in the Baltic Sea Region. It brought together various safety & security authorities, logistics operators and established knowledge partners. As a result of their collaboration, better preparedness and coordination to reduce damages in emergencies and post-emergency situations were achieved in the region.
HAZARD was also an amazing 3-year journey with the most wonderful crew. The book is a tribute to the various Partners whose expertise, cooperativeness and synergy not only enabled reaching the goals but made it fun and interesting as well.
Although HAZARD is now officially over, its legacy lives on in the form of enhanced safety & security procedures, various publications, enhanced expertise, new networks, and future projects. This book will pass on the learning experiences, outcomes and memories of HAZARD to future Project Partners of port safety & security undertakings.